Mineral Deposit Research: Meeting the Global Challenge 2005
DOI: 10.1007/3-540-27946-6_109
|View full text |Cite
|
Sign up to set email alerts
|

Pb-Zn-Cu mineralization in the Filfila Massif, northeastern Algeria

Abstract: The Filfila Massif, Algeria, comprises four stacked units. They are, from bottom to top, a para-autochthonous unit of limestone and dolomite, a metamorphic unit and its Tertiary cover, a peliticsandstone unit and an upper Numidian sandstone unit. The lower units have been intruded by the Filfila Granite.Fe, Cu and Cu-Pb-Zn sulphide mineralization is hosted by the Meçadjet vein set. The Meçadjet Vein is several hundred meters long and has a width of 0.5 to 3 m. It trends NE and dips 60° SE. This vein has cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Groundwater is one of the most precious natural resources in the north east of Algeria as it is the principal source of drinking water for the majority of the population. The groundwater aquifer of Skikda region is extremely susceptible to surface-derived contamination because of the high permeability of sands and gravels that compose the soil profile of East Skikda region [1][2][3]. Several studies in Skikda region reported various degradations levels of groundwater as one of the major concerns among the public and governmental decision makers [1][2][3][4], but these studies did not include a biochemical approach to evaluate groundwater contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is one of the most precious natural resources in the north east of Algeria as it is the principal source of drinking water for the majority of the population. The groundwater aquifer of Skikda region is extremely susceptible to surface-derived contamination because of the high permeability of sands and gravels that compose the soil profile of East Skikda region [1][2][3]. Several studies in Skikda region reported various degradations levels of groundwater as one of the major concerns among the public and governmental decision makers [1][2][3][4], but these studies did not include a biochemical approach to evaluate groundwater contamination.…”
Section: Introductionmentioning
confidence: 99%